Carnitine deficiency is associated with late-onset hypogonadism and depression in uremic men with hemodialysis. (December 2014) - Fukami, Kei; Yamagishi, Sho-ichi; Sakai, Kazuko; Kaida, Yusuke; Minami, Aki; Nakayama, Yosuke; Ando, Ryotaro; Obara, Nana; Ueda, Seiji; Wada, Yoshifumi; Okuda, Seiya
Abstract Late-onset hypogonadism (LOH) and depression contribute to cardiovascular disease (CVD) in male hemodialysis (HD) patients. Carnitine deficiency is frequently observed in HD patients, playing a role in CVD. We examined whether carnitine deficiency was independently associated with LOH and depression in these patients. Twenty-six male HD patients underwent determinations of serum levels of free carnitine and testosterone. Status of LOH and depression were evaluated by questionnaires using aging male symptoms' (AMS) scale and self-rating depression scale (SDS), respectively. Free carnitine and testosterone levels in male HD patients were significantly lower than those in age-matched healthy male subjects. Linear regression analysis showed that AMS scale was positively associated with SDS. Univariate regression analysis revealed that total carnitine (inversely), free carnitine (inversely) and HD duration were correlated with AMS scale. Multiple stepwise regression analysis revealed that free carnitine was an independent determinant of AMS scale. Furthermore, free carnitine was also independently correlated with SDS in male HD patients. This study demonstrated that decreased free carnitine levels were independently associated with AMS scale and SDS in male HD patients. The observations suggest that decreased free carnitine levels could be a marker and therapeutic target of LOH and depression in uremic men with HD.